Application of a Bentonite Slurry Modified by Polyvinyl Alcohol in the Cutoff of a Landfill - Guozhong Dai; Yanmin Sheng; Yutao Pan; Guicai Shi; Shujin Li (Advances in Civil Engineering)
Soil-bentonite cutoff walls are usually used to contain the contaminants of landfills. The pumpability, permeability, and adsorption capability of the slurry are all crucial to the performance of the cutoff wall. In this study, the effect of polyvinyl alcohol (PVA) was used to improve the performance of bentonite slurry. A series of lab tests were conducted to evaluate the pumpability, permeability, and adsorption capacity with different concentrations of PVA treatment. Results show that the addition of PVA can increase the fluidity and pumpable period of slurry, which facilitates the casting and grouting during construction. The addition of PVA also helps to reduce the permeability coefficient of slurry and improve the adsorption capability which enhances the cutoff performance of the walls.